Assessment on pollen carrying capacity and pollen viability of Elaeidobius kamerunicus (Coleoptera: Curculionidae) - MN, Dzulhelmi; Razi, Ahmad Norhisham; Kalog, Nur-Shafiqah Farhana; Murdi, Ahmad Afandi; Su, Suriyanti; Hazmi, Izfa Riza (University of the Philippines Los Banos, 2022)
Oil palm, also known as Elaeis guineensis Jacq (Arecales: Arecaceae), depends greatly on the pollinating weevil Elaeidobius kamerunicus (Coleoptera: Curculionidae) for fruit production. Despite this, information on the pollen-carrying capacity of E. kamerunicus is still lacking. This study assessed the pollen-carrying capacity (PCC) and pollen viability (PV) of E. kamerunicus in two oil palm plantations with different soil types in Sabah, Malaysia. The pollination contribution of adult weevils to sex and body surface area (BSA) was also investigated. Adult weevils were collected from both male and female inflorescences and kept in microcentrifuge tubes containing pollen grain germination medium solutions to assess their pollination contribution. Results indicated a significant difference for BSA between sexes. Mann-Whitney test showed greater PCC for male weevils than female weevils for FELDA Sahabat and Long Danau from male inflorescence. PCC for female inflorescence showed no significant differences between male and female weevils for both oil palm plantations. PV showed no significant difference between sexes but differed significantly between oil palm plantations due to better soil quality in clay textured soil. Based on the results, pollination contribution by male adult weevils was greater than female adult weevils for both plantations.